The Impact of Different Physiotherapy Programs on the Treatment of Low Back Pain - Vilma Dudonienė; Jurgita Radzevičiūtė (Lithuanian Sports University, 2020)
Low back pain is one of the biggest problems in modern world. Different physiotherapy programs are used for its treatment. Lumbar traction, has been used since the time of Hippocrates, but it is still the object of discussion. The purpose of this study was to determine the impact of traditional physiotherapy (control group), and traction therapy with TherapiMaster equipment (research group) on treatment of low back pain. Subjects: 40 patients from 34 to 62 years of age with low back pain participated in the study. Methods: static and dynamic trunk muscle endurance, low back pain intensity (according to Numeric Rating Scale, and McGill pain questionnaire), and functional state (according to Roland-Morris questionnaire, and Oswestry disability index) of patients were evaluated. Patients of control group received 14 procedures of traditional physiotherapy. The patients in the research group received 14 procedures of lumbar traction with TerapiMaster equipment and exercises. Conclusions: Physiotherapy procedures improved static and dynamic trunk muscle endurance in both control and research groups (p < 0.01), reduced low back pain (p < 0.01), and improved the patients' functional state in both groups (p < 0.01). The physiotherapy program with lumbar traction had better effect only relieving back pain assessed by McGill pain questionnaire compared to traditional physiotherapy (p < 0.05). Keywords: low back pain, lumbar traction, physiotherapy, Roland-Morris and McGill questionnaires, Oswestry disability index.